Efeitos demográficos do fogo de origem antrópica sobre espécies de fanerófitas do Cerrado - Vinícius Abreu Baggio (2022)
Anthropic fires, characterized by their high intensity, are increasingly frequent in the Cerrado. Population-level assessment of the responses of fire-affected plants is increasingly relevant when considering the conservation of these environments. In this study, we evaluated the demographic responses of five Cerrado species after a high-intensity fire that occurred in 2019 in Lagoa Santa, MG, Brazil. Three tree species, Stryphnodendron adstringes (Fabaceae), Connarus suberosus (Connaraceae), an unidentified Fabaceae and the palm Syagrus flexuosa (Arecaceae), were sampled three months after the fire in order to measure their first demographic responses. Two years later, Didymopanax macrocarpus (Araliaceae) was studied, with the aim of understanding long-term responses. Altogether, 527 individuals were sampled, with very high mortality rates of the aerial part (topkill), with the exception of S. flexuosa, a clonal plant, which quickly returned to producing inflorescences. The correlation between resprout production and plant size was significant in S. adstringes, C. suberosus and S. flexuosa punctuating the potential of height as a measure of nutrient storage for resprouts. Because it was sampled two years later, the species D. macrocarpus was the only one that showed resprouts with reproductive structures. The results showed that sampling immediately after the fire allows mortality estimates and reveals the potential for resprout production, while sampling further away from the moment of fire has the potential to reveal the competitive exclusion of some of the resprouts and the entry of survivors in reproductive stages. With the exception of S. flexuosa clones, none of the studied species would resist sequential fires for a long time, as the resprouts would not resist the fire and would consume carbohydrates stored in underground organs without due replacement time.